Pemanfaatan Pupuk Organik Nabati Berbasis Tanaman Lokal untuk Meningkatkan Pertumbuhan Hortikultura pada Musim Hujan - Dwitirta Mayasari; Nada Salwa; Siti Zulfiana; Baiq Sulfiana; Junaidi (Jurnal Pengabdian Masyarakat Sains Indonesia, 2026)
The rainy season often causes major problems in horticultural crops, including high humidity, fungal attacks, and weak vegetative growth. This field study developed a plant-based liquid organic fertilizer (LOF) using locally available materials such as moringa leaves, papaya leaves, sugar apple leaves, wax apple leaves, garlic, shallots, ginger, turmeric, galangal, and citronella. All ingredients were processed through roasting and blending techniques to produce an organic powder that dissolves easily in water. The fertilizer was applied through soil drenching and foliar spraying at doses of 1 tablespoon per liter of water for drenching and 1–2 tablespoons per 10 liters of water for spraying. Field observations showed significant improvements in plant height, leaf number, and stem diameter after treatment compared to before treatment. These results were supported by a paired-sample t-test at a significance level of 0.05, which indicated a p-value lower than 0.05. In addition, leaf color changed from pale green before treatment to dark green after treatment, indicating healthier plant conditions. During the generative phase, all observed parameters, including the number of flowers, number of fruits, and percentage of healthy fruits, showed significant increases. The findings suggest that locally sourced plant-based liquid organic fertilizer can effectively enhance the growth and productivity of horticultural crops during the rainy season.